Disruption of Autoregulatory Feedback by a Mutation in a Remote, Ultraconserved PAX6 Enhancer Causes Aniridia - Bhatia, Shipra (Elsevier, 2013)
The strictly regulated expression of most pleiotropic developmental control genes is critically dependent on the activity of long-range cis-regulatory elements. This was revealed by the identification of individuals with a genetic condition lacking coding-region mutations in the gene commonly associated with the disease but having a variety of nearby chromosomal abnormalities, collectively described as cis-ruption disease cases. The congenital eye malformation aniridia is caused by haploinsufficiency of the developmental regulator PAX6. We discovered a de novo point mutation in an ultraconserved cis-element located 150 kb downstream from PAX6 in an affected individual with intact coding region and chromosomal locus. The element SIMO acts as a strong enhancer in developing ocular structures. The mutation disrupts an autoregulatory PAX6 binding site, causing loss of enhancer activity, resulting in defective maintenance of PAX6 expression. These findings reveal a distinct regulatory mechanism for genetic disease by disruption of an autoregulatory feedback loop critical for maintenance of gene expression through development.